The changing impact of the active job openings-to-applicants ratio - Kamikawa, Yohei; Hanaki, Nao (PloS one, 2025)
Frequent ambulance dispatches is a common challenge in developed countries. Several factors have been identified as contributing to increase in dispatches, but no stipulation has explained the particular shift observed in Japan since 1995. This study examined ambulance dispatches in view of changes in a macroeconomic indicator. This longitudinal ecological study covered all annual ambulance dispatch incidents in Japan between 1980 and 2021 (42 years). The regression model comprised the active job openings-to-applicants ratio during deflation, the active job openings-to-applicants ratio during inflation, aging population trend, and mean ambient temperature, with the Japanese total population as an offset variable. There were a total of 177,042,244 ambulance dispatches during the study period. The active job openings-to-applicants ratio during deflation showed statistical significance in the regression analysis (generalized estimation equations estimate: 0.165, 95% confidence interval: 0.087 to 0.243) whereas the active job openings-to-applicants ratio during inflation did not (0.019, -0.021 to 0.059). The active job openings-to-applicants ratio during deflationary periods was associated with increased ambulance dispatches.